ENT 530 Social Media Portfolio: Tasty Brownies / Natasha Amira Azmi - Azmi, Natasha Amira (2020)
Digital marketing define as a marketing approach that primarily relies on the internet to connect with the target audience through various digital media channels and platforms. It means we use internet such as social media and websites to reach our customers. This medium can reach a large of customers as internet can connect all around the world. Most of us always spent our times scrolling social media such as Instagram, Twitter and Facebook. That is why the seller always uses this medium to sell their products as this medium also does not need capital to invest and it flexible as the time is depend on us. This report is about how we started a new business using online platform. For this assignment, we use Facebook as our business page to promote our business. Facebook is a widely use regardless of age. So, we can attract more customers to buy our products using online platform. Facebook is one of the medium that can engage with more customers as Facebook provide many information to the consumers. In addition, there are a few steps that we need to take to ensure that our promotion is successful such as teaser, soft sell and hard sell. This strategies need to be taken to attract customer’s attention towards our products. We need to identify which sentence or word that can attract customers to view our products and buy it. We need to capture customer’s attention in order to get engage with them. Therefore, we can learn how we want to started a new business, add knowledge in marketing, how we want to sustain engage with customers and how we can attract customer’s attention to buy our products.